EFFECT OF BOARD ATTRIBUTES ON FINANCIAL PERFORMANCE OF LISTED INSURANCE COMPANIES IN NIGERIA - A. O Ajisafe; A. O Isiaka; W Lawal; K.A Babatunde (Malete Journal of Accounting and Finance, 2023)
The continuous failure of companies around the world as a result of adverse strategic decisions made by the board, which had consequently affected the financial strength of companies, has raised questions on the effectiveness of board of directors. Therefore, this study examined the effect of board attributes on financial performance of listed insurance companies in Nigeria. The population of the study consists of thirty-four (34) listed insurance companies on the Nigerian Stock Exchange as at 31st December 2018 while twenty-three companies were used as sample due to the incomplete annual reports of some insurance companies. Random-effect regression analysis was employed in analyzing the secondary data obtained from the annual reports of the sampled companies for the period 2013-2018. The study found that board remuneration has significant negative effect on financial performance of listed insurance companies in Nigeria at 95% confidence level (p-value of 0.031) while board gender diversity has significant positive effect (p-value of 0.002) on financial performance of listed insurance companies in Nigeria. Therefore, this study concluded that board attributes have significant effect on financial performance of listed insurance companies in Nigeria. The study recommends that women should be given more consideration in board composition.